Expert System For Rating Of Ecotourism Sites Based On Safety, Health And Environmental Quality Assurance - Sehkaran, Vikneswaran Nair (2003)
The environment is the backbone of tourism products. Profitability in tourism depends on maintaining the attractiveness of tourist destinations with pleasant environment. Malaysia is a tropical country that is rich in a variety of ecological resources that of high tourism potential. Hence, the condition of the environment plays a critical role if the industry is to be sustained for future generations. The concept of ecotourismdatabase, which will keep record of all successful transactions. This research presents an efficient model using the Active Server Pages scripting method to manage and deliver the ecotourism rating expert system. emphasises the sites that has potential for ecological interest. Although the ecotourism industry in Malaysia has vast potential for further development, it has not received adequate attention. All ecotourism sites must be planned, guided and developed in a monitored and controlled manner for effective and efficient management. A systematic expert rating system is developed to maintain a certain level of standards based on different levels of categorisation to ensure the sustainability of ecotourism sites in Peninsular Malaysia. The expert system developed uses a Web-based information-sharing platform consistent with the existing legislation on safety, health and environment. The system is designed and developed on a back-end on-line database, which will keep record of all successful transactions. This research presents an efficient model using the Active Server Pages scripting method to manage and deliver the ecotourism rating expert system.